Reconceptualising the Juristic Legitimacy of Cash Waqf: A Ta‘Līlī Examination of Classical Doctrines and Their Integration into Modern Financial Systems - Muh. Zumar Aminuddin; Khoiruddin Nasution; Ali Sodiqin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This article aims to explore the arguments of Islamic legal scholars regarding the pros and cons of the concept of cash waqf and to contextualise these views in the reality of contemporary economic law. This study uses the ta‘līlī method with a thematic approach to classical fiqh literature to identify waqf themes and determine the ‘illah that forms the substance of the waqf concept. The literature analysis is then enriched with interviews with waqf experts and practitioners as a form of confirmation of the relevance of fiqh arguments in modern practice. The results of the study show that there are three main reasons used by scholars who support cash waqf, namely the applicability of 'urf (accepted social practice), the benefits generated, and the possibility of money being rented out or used productively. Meanwhile, scholars who reject cash waqf argue that money is manqūl (movable property) that is depleted when used, thus not fulfilling the requirement of permanence (ta'bīd) as an object of waqf. Interestingly, this study found that the concept of 'illah waqf is actually used by the group that rejects cash waqf, emphasising that money is not permanent because it will be depleted when used. However, this argument becomes less relevant in the context of the modern economy, where money functions not only as a medium of exchange but also as an investment instrument. When a cash waqf is managed productively within the financial system, its principal value can be maintained and even grow. Thus, the permanence of waqf does not lie in the physical form of the asset, but in the sustainability of its value and benefits. This study provides a practical contribution by emphasising that the management of cash waqf integrated with the modern financial system allows for the fulfilment of the principles of sustainability and benefit of waqf.